Гравитационная модель строения Авачинского вулкана (Камчатка) - Зубин М.И.; Козырев А.И. (Наука, 1989)
GRAVITATIONAL MODEL FOR THE AVACHA VOLCANO STRUCTURE (KAMCHATKA), by Zubin M. I. and Коzуrev A. I. This paper presents the results of gravimetric survey conducted at Avacha Volcano and adjacent territory. A model is constructed corresponding to the observed gravitational fields; it involves the peripheral magma chamber, the conduit and the zone of compaction in the somma. The position of tectonic disturbances and relative depth of the basement blocks were determined within the region of the Koryak-Avacha volcanic group.
Keywords: Авачинский